Convive contest (2006)
Next an interview with some of the participants of the CONVIVE contests of ideas and city-planning first draft of worthy housing, given in the month of July of the 2006. The interviews made here try to solve questions on the academic approach as well on the reflections that have resulted in that encounter. Bitácora has selected three of the participants with the purpose to explain the different methodologies from development of the contest, as well as the discussions derived from it.